Análise de temas recorrentes nas dissertações da linha de Informação e Comunicação do programa de Pós-Graduação em Design da UFMA - Serviliano, Bruno; Nehme, Laís Soares; Silva, Melissa Almeida (DAT Journal, 2021)
Information Design (D.I.) has a fundamental role in the transmission of messages of any kind and becomes inherent to citizenship, as its elements and methods have direct consequences on society. The scientific production in this area helps to consolidate it as a scientific field capable of cooperating for the development of soci- ety. Considering the importance of the D.I. and its impacts, this article had as its main objective to describe and analyze the dissertations of the research line of Information and Communication of the Post graduate Program in Design at the Federal University of Maranhão (UFMA), in order to investigate the processes that program students follow to study this field. The results were obtained through a literature review of 25 dissertations and identified the predominance of researches that study objects in digital support and with a qualitative approach. The most used methods and techniques were also observed.